Significance of Urban Green and Blue Spaces: Identifying and Valuing Provisioning Ecosystem Services in Dhaka City - Zinia, Naeema Jihan; McShane, Paul (European Journal of Sustainable Development, 2018)
We evaluated urban ecosystem services in Dhaka, Bangladesh, a city exposed to increasing urban congestion, air and water pollution, and climate change (particularly extreme weather events). Ecosystem services were evaluated from field-level observation, household surveys, in-depth interviews with experts and local citizens and literature review methods. Data analysis approaches included analysis of ecosystem services and market-price based valuation. The provisioning services provided by the household gardens (particularly rooftop gardens) offered direct economic benefits measurable as the production/value of goods (fruits and vegetables). The benefits to residents could exceed direct economic metrics to regulating services as urban vegetation can act to mitigate extreme heat encountered during the summer months. Our study quantified provisioning services provided by urban ecosystems including rooftop gardens, parks, and waterbodies. The selected urban ecosystems generated BDT 5.3 million (USD 68,465) worth services in 2016. The results of our research are expected influence citizens and policy makers for sustainable urban ecosystem management in Dhaka and similar climate- and population-exposed cities. Keywords: Urban Ecosystem, Green and blue spaces, Provisioning services, Valuation, City, Bangladesh